Torque efficiency of square and rectangular archwires into 0.018 and 0.022 in. conventional brackets - Spyridon N. Papageorgiou; Iosif Sifakakis; Ioannis Doulis; Theodore Eliades; Christoph Bourauel (SpringerOpen, 2016)
Abstract Background The aim of this study was to compare the torque efficacy of square and rectangular wires in 0.018- and 0.022-in. conventionally ligated brackets. Methods Brackets of the same prescription were evaluated in both slot dimensions. Identical acrylic resin models of the maxilla were bonded with the brackets and mounted on the Orthodontic Measurement and Simulation System. Ten 0.018 × 0.018 in., 0.018 × 0.022 in., and 0.018 × 0.025 in. stainless steel wires were evaluated in the 0.018-in. brackets and ten 0.019 × 0.019 in., 0.019 × 0.025 in., and 0.019 × 0.026 in. stainless steel wires were evaluated in the 0.022-in. brackets. A 15° buccal root torque was gradually applied to the right central incisor bracket, and the moments were recorded at this position. One-way ANOVA was applied for both bracket slot sizes along with post hoc analysis for the various archwire sizes. Results The mean measured moments varied between 10.78 and 30.60 Nmm among the assessed wire-and-bracket combinations. Both square and rectangular archwires in the 0.018-in. bracket system exerted statistically significantly higher moments in comparison with their counterparts in the 0.022-in. bracket system. Rectangular archwires exerted statistically significantly higher moments than square archwires, both for the 0.018- and the 0.022-in. bracket system. Conclusions Rectangular archwires seem to be more efficient in torque exertion, especially in 0.018-in. brackets.